Electrical safety in low voltage distribution systems up to 1000 V a.c. and 1500 V d.c. Equipment for testing, measuring ormonitoring of protective measures. Residual current devices (RCD) in TT, TN and IT systems Part 6, (15th September 1998) - British Standards Institution,
No abstract available